(untitled) (Medical Forum Monthly, 2024)
Objective: To evaluate the marginal integrity of silver amalgam and resin composite restorations in posterior teeth having Black’s class 1 carious lesion. Study Design: Perspective study Place and Duration of Study: This study was conducted at the Department of Operative Dentistry, Dental Section, Punjab Medical College Faisalabad and Fatima Memorial Hospital College of Dentistry, Lahore from October 2016 to March 2017. Patients and Methods: One hundred and sixty patients were selected having class 1 cavity in any of the mandibular molars. Radiographs were taken to assess the depth of cavity and periodontal status.78 patients got resin composite restorations while 86 patients received silver amalgam fillings. All the restorations were performed following standard isolation protocols. The success of the restorations was assessed after six months by considering the marginal integrity. This was checked by Cvar and Ryge criteria. Results: The Chi square statistic value that we observed with our statistical data with degree of freedom (df) 1 is 10.3385. The p-value captured by the analysis is 0.001. The result is significant at p<0.05. Conclusion: In perspective of successful restorations, good marginal integrity among all the restorations had predilection for the resin composite.